Immigration, criminal involvement, and violence in the U.S.: results from the National Epidemiologic Survey on alcohol and related Conditions-III - Moore, Kelly E. (Deviant behavior, 2021)
Topics of immigration and crime often receive national attention, despite evidence of the "immigrant paradox," in which immigrants have lower than expected crime and violence given their extreme social disadvantage. Research examining the immigrant paradox using an expanded set of crime outcomes and the latest available population data is needed. Using the National Epidemiologic Survey on Alcohol and Related Conditions Wave III data (2012-2013; n = 36,309), we analyzed the association between first-generation immigrant status alongside violence (i.e., other-directed, self-directed, victimization) and criminal involvement (i.e., crime, legal problems, incarceration) outcomes. Immigrants self-reported lower rates of all outcomes compared to U.S.-born adults, providing continued support for the immigrant paradox. Future research considering later generations of immigrants, as well as differential mechanisms through which immigrants and U.S.-born adults engage in violence and crime, is needed.